Assessment of the behavior of steel-fiber reinforced concrete produced with different ratios of fine-to-coarse aggregate - Açikgenç Ulaş, Merve; Alyamaç, Kürşat Esat; Ulucan, Zülfü Çınar (International Committee of the SCMT conferences, 2016)
Aggregate is an important ingredient of concrete that affects both fresh and hardened properties of concrete. The properties of concrete can be enhanced or worsened by changing properties of aggregate, especially particle size distribution of aggregate. However, in the literature, the effects of particle size distribution of aggregate on the properties of concrete have been neglected for particularly Steel-Fiber Reinforced Concrete (SFRC) although packing is a very important aspect for SFRC quality. Thus, this study investigates the effects of changing particle size distribution and maximum size (Dmax) of aggregate on the workability and mechanical properties of SFRC. With this aim, three gradations and two Dmax were used to produce SFRC mixtures with constant cement dosages and water/cement ratios. Totally, nine different concrete series were tested. To observe the properties of fresh concrete, Slump and Ve-Be tests were performed. The compressive, splitting tensile and flexural strengths of concretes were also evaluated, and the toughness of the SFRC specimens was calculated. Based on the test results, it can be concluded that the ratio of fine-to-coarse aggregate, the void content between the aggregate particles and Dmax have remarkable effects on the properties of both fresh and hardened SFRC. In addition, the toughness of the SFRC specimens which has constant cement dosage, and water/cement ratios were influenced by those aspects of the aggregates. © 2016 International Committee of the SCMT conferences. All rights reserved.
4th International Conference on Sustainable Construction Materials and Technologies, SCMT 2016 -- 7 August 2016 through 11 August 2016 -- Las Vegas -- 137590
Keywords: Aggregates; Cements; Concrete testing; Fiber reinforced materials; Hardening; Light transmission; Particle size; Particle size analysis; Size distribution; Steel fibers; Sustainable development; Aggregate particles; Coarse aggregates; Fresh and hardened properties; Properties of concretes; Properties of fresh concrete; Steel fiber reinforced concretes; Void contents; Water/cement ratio; Reinforced concrete